Unsuspected pulmonary embolism in lung cancer patients: Comparison of clinical characteristics and outcome with suspected pulmonary embolism - Shinagare, Atul B. (2012)
PURPOSE: Compare the clinical characteristics, rate of recurrent venous thromboembolism (VTE) and outcome of suspected and unsuspected pulmonary embolism (PE) detected on computed tomography in patients with lung cancer. METHODS: In this IRB-approved retrospective study, 77 patients [38 men, 39 women; mean age 64 (range, 35-90)] with lung cancer who developed PE between January 2004 and December 2009 were identified using research patient data registry and medical records. Patients with suspected (45/77,58%) and unsuspected (32/77,42%) PE were compared for the characteristics, treatment of PE, and rate of recurrent VTE using Fisher's exact test. The survival was compared using log-rank test, and Cox proportional hazards regression models were applied for univariate and multivariable analyses. RESULTS: Most cases of PE were found in patients undergoing chemotherapy (79%) and with metastatic disease (70%). Suspected PE more commonly involved main/lobar pulmonary arteries (33/45,73% vs. 9/32, 28%), while unsuspected PE more frequently involved of segmental/subsegmental arteries (p = 0.0001). All 11 cases of squamous cell carcinoma had suspected PE. Suspected and unsuspected PE did not differ in terms of age, gender, presence of metastatic disease at the time of PE or treatment for PE. 44/45 (98%) patients with suspected PE and 30/32 (94%) patients with unsuspected PE were treated for PE, mostly with anticoagulation (68/74,92%). Recurrent VTE was seen in 20% (9/45) of suspected PE and 19% (6/32) of unsuspected PE (p = 1.00). Median survival after PE was 5.6 months in suspected group and 6.2 month in unsuspected group, without significant difference by univariate or multivariate analyses. CONCLUSION: Although unsuspected PE more frequently involved peripheral pulmonary arteries, the treatments of PE, bleeding complications, rates of recurrent VTE, and survival after PE were similar for clinically suspected and unsuspected PE.